Integrating Sharia Principles with Environmental, Social, and Governance (ESG) Frameworks in Islamic Financial Institutions - Ahmad Rizani; Adelina Citradewi; Ubaydullayeva Go‘zalxon Murodqosim qizi (Green Economics: International Journal of Islamic and Economic Education, 2024)
The integration of Sharia principles with Environmental, Social, and Governance (ESG) frameworks presents a unique opportunity to enhance ethical accountability and sustainability in Islamic financial institutions. This study employs an analytical-descriptive research design, utilizing secondary data from annual sustainability reports, Sharia compliance documentation, and regulatory publications, to examine the adoption of ESG principles in the Islamic finance sector. Findings indicate that Islamic banks have achieved high levels of governance (90%) and social (85%) implementation, while environmental initiatives lag (62%), reflecting the need for stronger alignment with the khalifah fil ardh (stewardship of the earth) principle. The research also demonstrates a positive correlation between ESG implementation and investor confidence, with institutions exceeding 80% ESG adoption achieving an Investor Confidence Index of 92 points compared to 65 points among lower-performing banks. Despite conceptual synergy between ESG and Sharia principles centered on justice (adl), social welfare (maslahah), and environmental stewardship (khalifah) practical integration faces challenges including limited green financing instruments, regulatory fragmentation, and insufficient standardized ESG reporting tailored to Islamic finance. To address these issues, the study proposes an integrative ESG Sharia model emphasizing ethical foundations as the core of sustainable practices. Recommendations include developing Maqasid al-Shariah–based ESG indicators, expanding engagement in green financing and renewable energy projects, and adopting digital sustainability reporting. This integrative approach supports both global sustainability goals and the ethical imperatives of Islamic finance, contributing to a value-based, socially responsible, and spiritually aware financial ecosystem.